Empires of Panic : Epidemics and Colonial Anxieties - Peckham, Robert (Book collections on Project MUSE., 2015)
Empires of Panic is the first book to explore how panics have been historically produced, defined, and managed across different colonial, imperial, and post-imperial settings--from early nineteenth-century East Asia to twenty-first-century America. Contributors consider panic in relation to colonial anxieties, rumors, indigenous resistance, and crises, particularly in relation to epidemic disease. How did Western government agencies, policymakers, planners, and other authorities understand, deal with, and neutralize panics? What role did evolving technologies of communication play in the amplification of local panics into global events? Engaging with these questions, the book challenges conventional histories to show how intensifying processes of intelligence gathering did not consolidate empire, but rather served to produce critical uncertainties--the uneven terrain of imperial panic.